Pengaruh Inisiasi Menyusu Dini Terhadap Suhu Tubuh Bayi Baru Lahir - Yuni Astari, Ruri (Jurnal Keperawatan Bina Sehat, 2012)
ABSTRACTHypothermia is one cause of mortality and morbidity in newborn. This is caused by the fact that the babys body surface area is larger than an adults body surface and the rate of heat loss even faster. One handling of heat loss (hypothermia) is by early breastfeeding initiation (IMD). IMD gives opportunity for baby to suckle his mother early in life. One of the benefits of IMD is to prevent heat loss (hypothermia).The purpose of this study was to determine the effect of early breastfeeding initiation against newborn body temperature at BPS Hj. Yayah Surlan Kuningan Sub-District and  BPS Yetti Sudiati Cilimus Sub-District Kuningan Regency in 2011. This study used a pure experiment research design to conduct a simple experiment (Post-test Only Control Group Design). Its population was newborns at BPS Hj. Yayah Surlan and BPS Hj. Yetti Sudiati. The number of samples as many as 47 of each group. Which 47 infants in the intervention group and 47 infants in the control group. This study used a simple random sampling with the criteria that the labor is a normal birth without complications.This study used the same homogeneity of variance test. Because the ρ value wasobtained through the Levene test for 0.120> α. The average temperature of infants in the intervention group was 36.7° C, while the average temperature of infants in the control group was 36.47°C. The results of statistical tests of the effect of early breastfeeding initiation on the incidence of hypothermia after the intervention obtained the value of Pvalue = 0.0001 (<0.05). It can be concluded that there was a statistically significant difference in the average temperature of newborns who did not experience IMD, and in other words there was an influence on the newborn temperature. It is therefore expected for the midwives to provide care to newborn in the form of early breastfeeding initiation to prevent heat loss (hypothermia) in newborns.Keywords: Early Breastfeeding Initiation, Newborn Body Temperature, hypothermia